Enhancing Reading Comprehension through Visual Information: A Longitudinal Study in Higher Education - Putri Asilestari; Raffly Henjilito; Vitri Angraini Hardi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Reading comprehension is a critical component of academic achievement, yet many English as a Foreign Language (EFL) learners face challenges in processing complex texts. This study investigates the impact of visual information-based reading materials on improving comprehension among Indonesian EFL university students. A mixed-methods, cross-sectional design was employed over three academic semesters. A total of 228 students were assigned to either an experimental group, which received reading materials incorporating visual elements, or a control group, which received text-only materials. Quantitative data were collected using standardized comprehension assessments, while qualitative insights were gathered through student reflections and interviews. The experimental group demonstrated significantly higher performance in literal comprehension compared to the control group (p 0.05, Cohen’s d = 0.81), indicating a large effect size. Qualitative data reinforced these findings, revealing that visual aids enhanced student engagement, understanding, and information retention. The integration of visual elements into reading materials effectively supports comprehension in EFL contexts. Visual information appears to reduce cognitive load and facilitate meaning-making, particularly in learners processing texts in a non-native language. Visual-enhanced reading materials significantly improve literal comprehension among Indonesian EFL university students. These findings underscore the importance of incorporating visual literacy strategies in EFL pedagogy and call for further research into interactive and digital visual tools to support reading comprehension.